The men who built America (A & E Television Networks, 2012)
Vanderbilt, Rockefeller, Carnegie, Morgan, Ford, and the men who built America. Meet the titans who forged the foundation of modern America and created the American Dream. The miniseries shines a spotlight on the influential builders, dreamers, and believers whose feats transformed the United States.